In Vitro Growth Response of Porang (Amorphophallus muelleri Blume) Bulbil to Kinetin Concentration - Normasari, Rut (Jurnal Biologi Tropis, 2025)
The plant known as porang (Amorphophallus muelleri Blume) has a high glucomannan content in its tubers. The availability of porang seeds is one of the elements influencing porang production, hence tissue culture must be developed to improve seed procurement. For porang seed propagation to be successful in vitro, growth regulators must be added. This study aims to determine the effect of adding kinetin concentration on porang shoot induction. Five treatments the addition of kinetin at doses of 0, 1, 2, 3, and 4 mg/L were included in the Non-Factorial Completely Randomized Design (CRD) experiment. All observation variables, including explant growth, shoot emergence time, percentage of shoots created, total number of shoots, and number of shoots per explant, were found to be significantly impacted by the addition of kinetin. With a shoot emergence time of 21.86 days after inoculation, 96% of the shoots produced, a total number of 108.80 shoots, and a number of shoots of 22.75 per explant, kinetin 4 mg/L was the optimal concentration for porang shoot induction.